2013
DOI: 10.33073/pjm-2013-042
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous or Exogenous Origin of Vaginal Candidiasis in Polish Women?

Abstract: Vaginal candidiasis is a common problem of clinical practice. Many studies have been conducted to explain its origin but only a few have included Polish women. The aim of the study was to determine the prevalence and similarity of oral, anal and vaginal Candida albicans strains isolated from Polish women with vaginal candidiasis. The study involved 20 from 37 recruited women. Swab samples were collected from their vagina, anus, and oral cavity at two-month intervals. All the women were treated with nystatin. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Other researchers have found that carriage of rectal Candida was higher during episodes of vulvo-vaginitis than during periods of remission. 8 Dynamic transmission of yeast by autoinoculation has been documented, 16 emphasizing the potential importance of extra-vaginal carriage, and justifying the use of oral fluconazole maintenance therapy to reduce recurrence rates in women with RVVC. 4 5 However, it does not explain why, according to our findings, systemic therapy failed to prevent Candida vulvo-vaginitis relapses in anal Candida carriers.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Other researchers have found that carriage of rectal Candida was higher during episodes of vulvo-vaginitis than during periods of remission. 8 Dynamic transmission of yeast by autoinoculation has been documented, 16 emphasizing the potential importance of extra-vaginal carriage, and justifying the use of oral fluconazole maintenance therapy to reduce recurrence rates in women with RVVC. 4 5 However, it does not explain why, according to our findings, systemic therapy failed to prevent Candida vulvo-vaginitis relapses in anal Candida carriers.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…yeasts. The ability to colonize tissue and the nature of infections caused by yeasts depends on the strain-specific features including invasiveness, adhesion and biofilm creation abilities, enzymatic activity and the immune status of the host [1][2][3][4][5][6]. Candida albicans is the main pathogenic species and the most frequent cause of candidiasis in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans is responsible for 80% -92% of all vulvovaginal candidiasis cases (VVC) [5]- [7]. However, the frequency of other species as causative agents for this disease is increasing, particularly those with different susceptibility profiles to antifungal agents, possibly because of the indiscriminate use or misuse of these drugs, which may result in recurrent infections [8]- [11].…”
Section: Introductionmentioning
confidence: 99%